Overview of Anxiety Levels Among the Elderly at Puskesmas Haur Gading, Kota Amuntai - Agustiana, Faulita; Tasalim, Rian (Universitas Ibn Khaldun Bogor, 2025)
The elderly are vulnerable to psychological disorders such as anxiety, which negatively impact their quality of life. The increasing number of elderly people in Indonesia, including in Kota Amuntai, highlights the importance of focusing on their mental health. Unfortunately, mental health facilities and services for the elderly at Puskesmas Haur Gading remain limited. This study aims to describe the anxiety levels of the elderly at Puskesmas Haur Gading. The research method used is descriptive quantitative with a cross-sectional approach. The study sample consisted of 40 elderly individuals aged 60 and over, selected through purposive sampling. The instrument used was the Hamilton Rating Scale for Anxiety (HRS-A) questionnaire, and the data were analyzed using frequency distribution and percentage.The results showed that 47.5% of respondents experienced moderate anxiety, 30% mild anxiety, 17.5% had no anxiety, and 5% experienced severe anxiety. Factors such as social support, physical health, and access to healthcare services influenced respondents' anxiety levels. In conclusion, the majority of elderly at Puskesmas Haur Gading experienced moderate anxiety. Comprehensive interventions, including family and community support, and improved mental health services, are needed to reduce anxiety levels among the elderly in this area.